The Role of Service Quality in E-Commerce Customer Satisfaction and Loyalty - Nabila, Putri Izatin; Rahayu, Siti; Widjaja, Fitri Novika (LP2M IAIN Palopo, 2026)
This study examines the influence of service quality on customer satisfaction and customer loyalty among Millennial and Gen Z users of e-commerce platforms in Indonesia. Using a quantitative explanatory approach, data were collected from 200 respondents who actively shopped online through major platforms such as Shopee, Tokopedia, Lazada, Blibli, and TikTok Shop. Service quality was measured using four e-servqual dimensions: efficiency, fulfillment, system availability, and privacy. Data were analyzed using PLS-SEM through SmartPLS to evaluate the measurement and structural models. The findings reveal that efficiency and fulfillment significantly increase customer satisfaction, while fulfillment and privacy significantly influence customer loyalty. Meanwhile, system availability shows no significant effect on either satisfaction or loyalty, indicating that users perceive it as a basic feature rather than a determinant of experience. The results also demonstrate that customer satisfaction strongly predicts customer loyalty, emphasizing its mediating role in the relationship between service quality and loyalty. Overall, the study highlights the importance of efficient service, accurate fulfillment, and strong privacy protection in retaining e-commerce users from younger generations.